(untitled) - Illusie, Luc (Comptes Rendus. Mathématique, 2025)
I discuss some of the contributions that Grothendieck brought to differential calculus in the 1960s (infinitesimal neighborhoods, algebraic de Rham cohomology, crystalline cohomology) and sketch a few recent developments.